If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+3)/(3x-1)=1
We move all terms to the left:
(x+3)/(3x-1)-(1)=0
Domain of the equation: (3x-1)!=0We multiply all the terms by the denominator
We move all terms containing x to the left, all other terms to the right
3x!=1
x!=1/3
x!=1/3
x∈R
(x+3)-1*(3x-1)=0
We get rid of parentheses
x-1*(3x-1)+3=0
We move all terms containing x to the left, all other terms to the right
x-1*(3x-1)=-3
| (x+3)/3x-1=1 | | 5(2x-1)=4x+2(x+5)-3 | | 20-3s=-10-6s | | 7x2-90x-112=0 | | 20-3=-10-6s | | (x+8)/5=x-8 | | -2(50-6x)=4(2x+12) | | -2(50-6x)=4(2x+12 | | 5x-2(5x-2)=4x+5 | | 3d=-18=d | | 2x+(x-4)=0 | | 0r-7=r+5 | | 8(x-4)-6(x+9)=9(x+11)-8(x-5) | | 2(2+x)+(4x-1)×3=10x-7 | | -5y+8=2 | | 4(t+4=116t-72-68t | | (2x-1)(3x-6)=0 | | 15q=24-9q | | 5x+4=9x+9 | | 7x-13=8x+10 | | 2x-4x=123 | | 7−x/7=−2 | | xxx-25=0 | | 31p-4+25p=2+42p | | 7-7f=9-8f | | 5h+5h=9h | | x+6+8=2x-x+14x+6+8=2x−x+14 | | 4(5x+2)=5(1-2x)+33 | | 4y’’–8y’+3y=0;y(0)=1;y’(0)=-1 | | x/12=11/12 | | X2-y2=52 | | x/12-2/3=1/4 |